Acupuncture vs. Pharmacological Prophylaxis of Migraine: A Systematic Review of Randomized Controlled Trials - Giovanardi, Carlo Maria; Cinquini, Michela; Aguggia, Marco; Allais, Gianni; Campesato, Manuela; Cevoli, Sabina; Gentili, Fabio; Matrà, Annunzio; Minozzi, Silvia (Frontiers in Neurology, 2020)
Introduction: Migraine is a chronic paroxymal neurological disorder characterised by attacks of moderate to severe headache and reversible neurological and systemic symptoms. Treatment of migraine includes acute therapies, that aim to reduce the intensity of pain of each attack, and preventive therapies that should decrease the frequency of headache recurrence. The objective of this systematic review was to assess the efficacy and safety of acupuncture for the prophylaxis of episodic or chronic migraine in adult patients compared to pharmacological treatment. Methods: We included randomized-controlled trials published in western languages that compared any treatment involving needle insertion (with or without manual or electrical stimulation) at acupuncture points, pain points or trigger points, with any pharmacological prophylaxis in adult (≥ 18 years) with chronic or episodic migraine with or without aura according to the criteria of the International Headache Society. Results: 9 randomized trials were included encompassing 1484 patients. At the end of intervention we found a small reduction in favour of acupuncture for the number of days with migraine per month: (MD: -1.14; 95%CI -1.94 to -0.33), and for response rate (RR: 1.46; 95%CI 1.16 to 1.84). We found a moderate effect in the reduction of pain intensity in favour of acupuncture (SMD: -0.36 ;95%CI -0.60 to -0.13), and a large reduction in favour of acupuncture in both the dropout rate due to any reason (RR 0.39; 95%CI 0.18 to 0.84) and the dropout rate due to adverse event (RR 0.26; 95%CI 0.09 to 0.74). Quality of evidence was moderate for all these primary outcomes. Results at longest follow-up confirmed these effects. Conclusions: Based on moderate certainty of evidence, we conclude that acupuncture is mildly more effective and much safer than medication for the prophylaxis of migraine.